Evaluation of dynamic properties of gas pumping units according to the results of experimental researches - Gorbiychuk, Mykhailo; Zamikhovska, Olena; Zamikhovskyi, Leonid; Zikratyi, Serhii; Shtaier, Lidiia (Eastern-European Journal of Enterprise Technologies, 2019)
Experimental studies of the dynamic properties of gas pumping units (GPU) of various types, which allowed us to obtain GPU acceleration curves and determine the parameters of the transfer function through various transmission channels of input effects, are conducted. For this, a method and a software product were developed for implementing the procedure for determining the areas of the k orders through the moments of the auxiliary function. As a result of the experiments performed on operating GPU, the acceleration characteristics of the selected signal transmission channels were obtained. To identify the dynamic properties of the GPU, a software product was developed in the MatLab environment, which in iterative mode allows each acceleration curve to be approximated by the transfer function, the order of which is selected by the user. The iterative mode allows the user to select the order of the polynomials of the numerator and denominator of the transfer function, and also to calculate the numerical values of the parameters of the selected transfer function. The software product was tested on industrial data obtained during normal start-up of theGPU. The obtained results can be used in the development of a new method for monitoringthe reliability and diagnosing the technical state of automatic control systems (ACS) of the gas pumping units and its components. The essence of the method is that a change in the technical state of the ACS or GPU affects their dynamic properties, and this, in turn, causes a change in the parameters of the transfer functions, which can be recorded after a certain period of time. Determining the ranges of values of the transfer function coefficients for various technical states of different types of ACS and GPU, it will be possible to predict the period of their operation in the future